Comparative Analysis of the Effects of Managerial and Performance Dimensions of Rural Producers’ Cooperatives in Iran - Maryam Najafi; Hedayat Nouri; Amir Mozafar Amini (SAGE Open)
The purpose of this study is to analyze the importance of management dimensions as well as the performance dimensions of rural producers’ cooperatives on the overall performance of rural producers’ cooperatives in Isfahan province. The statistical population of this research is the components of rural producers’ cooperatives in Isfahan province. Required data were collected by completing the questionnaire by 375 persons from rural cooperatives. In this study, principal component analysis (PCA), linear regression analysis, and arithmetic mean method were used. The results of the research indicated that a unit of improvement in cooperative management led to a 67% improvement in cooperatives performance. Among the seven component dimensions of cooperatives performance, the improvement of livelihood (0.852), had the highest factor loading in the performance structure of rural cooperatives. Also, among the four component dimensions of co-operative management, the leading (0.895) has been the most important factor in the management structure of rural producers’ cooperatives.